An Error Analysis of Orthographic Representation in Written Chinese Characters - Wee-Ling, Kuan (UNIMAS Publisher, 2021)
This paper reports an error analysis of orthographic representation in written Chinese characters among Mandarin as foreign language (MFL) learners studying at an elementary level at a Malaysian public university in their dictation assessment. A total of 262 stroke error types of their orthographic representation in written Chinese characters were collected and analysed. The errors were consequently classified into four main categories among 165 MFL learners who took part in the study. The study found that participants made most mistakes in the stroke numbers and shape of orthographic representation in written Chinese characters. It was also found that there were detectable mistakes in stroke relation and stroke direction of orthographic representation in written Chinese characters. The cognitive factors contributing to the orthographic representation error types in written Chinese characters are discussed. It is concluded that beginner MFL learners would have a greater tendency to commit several character errors in writing Mandarin because of their low level of orthographic awareness and presumably a high cognitive load given to them as they transit from writing alphabets scripts to writing Chinese characters. Future research could examine how MFL learners cognitively adapt when transitioning from alphabet scripts to Chinese characters. Findings would guide instructors in the teaching Chinese characters more efficient and subsequently, it would allow them to interpret orthographic representations and write Chinese characters more accurately.